Capital Controls and the Icelandic Banking Collapse: an Assessment - McCombie, JSL; Spreafico, MRM (Palgrave Macmillan, 2016)
This is the author accepted manuscript. The final version is available from Palgrave Macmillan via https://doi.org/10.1007/978-3-319-41219-1_6 This paper reassesses the causes and consequences of the Icelandic banking collapse of 2008. It examines the reasons behind the rapid growth of the recently privatized banks over the subsequent few years, the lack of prudential regulation and the high risk loan strategy of the banks. These, together with the inevitable failure of the Central Bank of Iceland to act as a lender of last resort of foreign currency, made the collapse of the financial system almost inevitable. The IMF was called in and a notable aspect of its rescue package was the imposition of capital controls. This can be seen as the culmination of a secular change of the IMF’s attitude to the regulation of cross-border financial flows. The paper presents an assessment of how effective this strategy has been. It concludes with a more general discussion of the political economy of capital controls.